2024
DOI: 10.1002/cam4.6800
|View full text |Cite
|
Sign up to set email alerts
|

RGD peptide in cancer targeting: Benefits, challenges, solutions, and possible integrin–RGD interactions

Hossein Javid,
Mahsa Akbari Oryani,
Nastaran Rezagholinejad
et al.

Abstract: RGD peptide can be found in cell adhesion and signaling proteins, such as fibronectin, vitronectin, and fibrinogen. RGD peptides' principal function is to facilitate cell adhesion by interacting with integrin receptors on the cell surface. They have been intensively researched for use in biotechnology and medicine, including incorporation into biomaterials, conjugation to medicinal molecules or nanoparticles, and labeling with imaging agents. RGD peptides can be utilized to specifically target cancer cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(1 citation statement)
references
References 263 publications
(667 reference statements)
0
1
0
Order By: Relevance
“…It is suggested that negatively charged heparan sulfate chains branching from proteoglycan (HSPG) on the cell surface induce receptor-mediated endocytosis as a receptor for cationic CPPs [ 14 ]. RGD peptides (Arg-Gly-Asp), as representative THPs, specifically target cancer cells by binding to ανβ3 and ανβ5 integrins [ 15 ]. NGR peptides (Asn-Gly-Arg) bind to the receptor aminopeptidase N [ 16 ].…”
mentioning
confidence: 99%
“…It is suggested that negatively charged heparan sulfate chains branching from proteoglycan (HSPG) on the cell surface induce receptor-mediated endocytosis as a receptor for cationic CPPs [ 14 ]. RGD peptides (Arg-Gly-Asp), as representative THPs, specifically target cancer cells by binding to ανβ3 and ανβ5 integrins [ 15 ]. NGR peptides (Asn-Gly-Arg) bind to the receptor aminopeptidase N [ 16 ].…”
mentioning
confidence: 99%